Bagwere Cultural Interpretation of Physical-Disability Before and During Disability Inclusion - Musenyente, Elijah; Wamanga, Doreen (INKLUSI, 2023)
This study investigates how the Bagwere people, an ethnic group in eastern Uganda, interpret physical disabilities in their culture, both before and after the introduction of disability inclusion policies and practices. The study uses a qualitative research method to collect data from 30 participants, half of whom have physical disabilities and half of whom do not. The article analyzes the data using thematic analysis and reveals that the Bagwere culture has negative attitudes and beliefs towards physical disabilities, which affect the social inclusion and well-being of persons with physical disabilities. The article also examines the impact of the legal framework and the historical context of disability inclusion in Uganda and globally on the Bagwere culture. The article concludes with some recommendations for improving the cultural and social inclusion of persons with physical disabilities in Uganda. Penelitian ini menginvestigasi bagaimana masyarakat Bagwere, sebuah kelompok etnis di Uganda bagian timur, menafsirkan disabilitas fisik dalam budaya mereka, baik sebelum dan sesudah diperkenalkannya kebijakan dan praktik inklusi disabilitas. Penelitian ini menggunakan metode penelitian kualitatif untuk mengumpulkan data dari 30 partisipan, separuhnya memiliki disabilitas fisik dan separuhnya lagi tidak. Data yang dikumpulkan dianalisis secara tematik dan mengungkapkan bahwa budaya Bagwere memiliki sikap dan keyakinan negatif terhadap disabilitas fisik, yang berdampak pada inklusi sosial dan kesejahteraan penyandang disabilitas fisik. Artikel ini juga mengkaji dampak kerangka hukum dan konteks historis inklusi disabilitas di Uganda dan secara global terhadap budaya Bagwere. Beberapa rekomendasi diusulkan untuk meningkatkan inklusi budaya dan sosial bagi penyandang disabilitas fisik di Uganda.